2010
DOI: 10.1534/genetics.110.116806
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Regulation of Mlh1p Heterodimers in Meiosis and Mitosis in Saccharomyces cerevisiae

Abstract: Mlh1p forms three heterodimers that are important for mismatch repair (Mlh1p/Pms1p), crossing over during meiosis (Mlh1p/Mlh3p), and channeling crossover events into a specific pathway (Mlh1p/Mlh2p). All four proteins contain highly conserved ATPase domains and Pms1p has endonuclease activity. Studies of the functional requirements for Mlh1p/Pms1p in Saccharomyces cerevisae revealed an asymmetric contribution of the ATPase domains to repairing mismatches. Here we investigate the functional requirements of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 48 publications
(76 reference statements)
3
10
1
Order By: Relevance
“…mlh3-K83A strains showed a wild-type phenotype (Table 3). Our results for the mlh3-N35A and mlh3-G97A mutations were similar to those obtained by Cotton et al (2010). However, for mlh3-E31A , which is thought to disrupt ATP hydrolysis by the Mlh3 subunit, we observed a null MMR phenotype; Cotton et al (2010) observed a close to wild-type phenotype for this mutant.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…mlh3-K83A strains showed a wild-type phenotype (Table 3). Our results for the mlh3-N35A and mlh3-G97A mutations were similar to those obtained by Cotton et al (2010). However, for mlh3-E31A , which is thought to disrupt ATP hydrolysis by the Mlh3 subunit, we observed a null MMR phenotype; Cotton et al (2010) observed a close to wild-type phenotype for this mutant.…”
Section: Resultssupporting
confidence: 86%
“…mlh1-E31A and mlh1-K84A , however, conferred MMR phenotypes that were different from their equivalent mlh3 mutations, with mlh1-E31A strains appearing more proficient in MMR and mlh1-K84A strains less proficient [Tables 3 and 4 (Tran and Liskay 2000; Hoffman et al 2003; Wanat et al 2007; Argueso et al 2003)]. Thus our work, in conjunction with previous studies, reinforces the hypothesis that the subunits of MLH complexes provide unique contributions to MMR (Tran and Liskay 2000; Hall et al 2002; Argueso et al 2003; Hoffman et al 2003; Wanat et al 2007; Nishant et al 2008; Cotton et al 2010). …”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations